Diversity, Interaction, and Bioprospecting of Plant-Associated Microbiomes - Jacquelinne J. Acuña; Milko A. Jorquera (Diversity, 2020)
Plant-associated microbiomes have been suggested as pivotal for the growth and health of natural vegetation and agronomic plants. In this sense, plant-associated microbiomes harbor a huge diversity of microorganisms (such as bacteria and fungi) which can modulate the plant host response against pathogens and changing environmental conditions through a complex network of genetic, biochemical, physical, and metabolomics interactions. Advances on next-generation omic technologies have opened the possibility to unravel this complex microbial diversity and their interactive networks as never described before. In parallel, the develop of novel culture-dependent methods are also crucial to the study of the biology of members of plant-associated microbiomes and their bioprospecting as sources of bioactive compounds, or as tools to improve the productivity of agriculture. This Special Issue aims to motivate and collect recent studies which are focused on exploring the diversity and ecology of plant-associated microbiomes and their genetic and metabolic interactions with other microorganisms or their plant hosts, as well as their potential biotechnological applications in diverse fields, such as inoculants for agriculture.